Legal Axiology: General Characteristics - Safaryan, Garnik; Ikilikyan, Arthur (NAS RA)
This scientific article explores the meaning of legal axiology as a doctrine about the values of law, the legal (value-legal) meaning of law (positive law), and the state. The author examines both legal (positivist) and natural law approaches to legal axiology, emphasizing the features of these concepts. Additionally, the article considers the concepts of equality, freedom, and justice, determined by the principle of formal equality of participants in this form of relations. The author also presents the viewpoints of famous philosophers and jurists on legal axiology, including G. Hegel, I. Kant, H. Kelsen, etc.
Keywords: Legal Studies